Molecular Characterization of the Complete 23F Capsular Polysaccharide Locus of Streptococcus pneumoniae - Ramirez, Mario (American Society for Microbiology (ASM), 1998)
The complete DNA sequence of the capsular locus 23F of Streptococcus pneumoniae is presented. The 18.6-kb cps23f locus is composed of 18 open reading frames flanked at the 5′ and 3′ ends by the genes dexB and aliA, an arrangement similar to those of some of the other identified cps loci.